Apical Periodontitis in Vital and Nonvital Teeth: Clinical and Radiographic Features - Asgary , Saeed; Aminoshariae , Anita; Wesselink , Paul R (Iranian Endodontic Journal, 2024)
Apical periodontitis (AP) is a common inflammatory condition predominantly caused by the response of the immune system to microbial invasion within the root canal system. Contrary to conventional perception, AP may occur in vital teeth with inflamed pulp; adding complexity to diagnosis and treatment. AP, due to its frequent lack of symptoms and reliance on radiographic evaluation for detection, often presents diagnostic challenges. In addition, AP pathogenesis involves complex interactions between microbial virulence and host immune response at the cellular and molecular levels. Comprehensive diagnostic procedures, including patient history, clinical examination, and radiographic evaluation, are essential for early detection and necessary intervention, with the recognition of clinical signs and symptoms underscoring the importance of regular dental evaluations. The current review primarily discusses the radiographic and clinical features of AP in vital and non-vital teeth; introducing a new taxonomic classification to improve diagnostic precision and treatment outcomes. Moreover, it proposes different treatment categories/options for the management of AP, based on pulp status as well as clinical and radiographic findings; emphasizing vital pulp therapy and root canal treatment for vital and non-vital teeth with AP, respectively. Furthermore, the global and regional epidemiology of AP is presented, along with its association with systemic health conditions; e.g., cardiovascular diseases, diabetes mellitus, and adverse pregnancy outcomes. Moreover, future research directions are advocated to improve the efficacy and predictability of diagnosis and treatments; paving the path for clinicians in early detection, accurate diagnosis, and effective management of AP to enhance oral health outcomes.